Multiple transmissions of de novo mutations in families - Jónsson, Hákon; Sulem, Patrick; Arnadottir, Gudny A.; Pálsson, Gunnar; Eggertsson, Hannes P.; Kristmundsdottir, Snaedis; Zink, Florian; Kehr, Birte; Hjorleifsson, Kristjan E.; Jensson, Brynjar Ö.; Jonsdottir, Ingileif; Marelsson, Sigurdur Einar; et al. (Nature genetics, 2018)
De novo mutations (DNMs) cause a large proportion of severe rare diseases of childhood. DNMs that occur early may result in mosaicism of both somatic and germ cells. Such early mutations can cause recurrence of disease. We scanned 1,007 sibling pairs from 251 families and identified 878 DNMs shared by siblings (ssDNMs) at 448 genomic sites. We estimated DNM recurrence probability based on parental mosaicism, sharing of DNMs among siblings, parent-of-origin, mutation type and genomic position. We detected 57.2% of ssDNMs in the parental blood. The recurrence probability of a DNM decreases by 2.27% per year for paternal DNMs and 1.78% per year for maternal DNMs. Maternal ssDNMs are more likely to be T>C mutations than paternal ssDNMs, and less likely to be C>T mutations. Depending on the properties of the DNM, the recurrence probability ranges from 0.011% to 28.5%. We have launched an online calculator to allow estimation of DNM recurrence probability for research purposes. Analysis of 1,007 sibling pairs from 251 families identifies 878 de novo mutations shared by siblings at 448 sites. Recurrence probability based on parental somatic mosaicism, sibling sharing, parent of origin, mutation type and genomic position can range from 0.011% to 28.5%.